Why do we need a national address point database to improve wildfire public safety in the U.S.?. (October 2019) - Li, Dapeng; Cova, Thomas J.; Dennison, Philip E.; Wan, Neng; Nguyen, Quynh C.; Siebeneck, Laura K.
Abstract: The aim of this paper is to advance understanding of the value of national address point databases in improving wildfire public safety in the U.S. The paper begins with a review of the value of a national address point database in wildfire evacuations. An introduction to address point data in the U.S. is presented by examining two national address point datasets—the National Address Database and the OpenAddresses project. We examine the existing and potential uses of address point data in wildfire evacuation research and practice. Specifically, we cover four primary applications: wildland-urban interface mapping, wildfire evacuation warnings/zoning, wildfire evacuation traffic simulation, and house loss assessment/notification. Based on our review, we find that address point data has the potential to significantly improve these applications and a national address point database can help enhance wildfire public safety in the U.S. Finally, we conclude with a discussion of the challenges of using address point data in wildfire evacuations and future research directions. This review proposes an agenda for further research on the potential use of address point data in wildfire evacuation applications and sheds light on the development and applications of the two national address point database projects. Highlights: The need for address point data in wildfire evacuation in the U.S. is increasing. The OpenAddresses and the National Address Database project are the primary national address databases in the U.S. A national address point database can be used in many wildfire evacuation applications to maximize public safety. Further research still needs to be conducted on the development and applications of national address point databases.